Factors associated with routine childhood vaccine uptake and reasons for non-vaccination in India: 1998–2008. Issue 44 (22nd October 2018) - Francis, Mark Rohit; Nohynek, Hanna; Larson, Heidi; Balraj, Vinohar; Mohan, Venkata Raghava; Kang, Gagandeep; Nuorti, J. Pekka
Highlights: Disparities in vaccine uptake were associated with many maternal and socio-demographic characteristics. Gaps in awareness, acceptance and affordability were underlying reasons for non-vaccination. Need to address parental fears and increase trust to improve uptake of routine vaccinations in India. Abstract: Background: Despite almost three decades of the Universal Immunization Program in India, a little more than half the children aged 12–23 months receive the full schedule of routine vaccinations. We examined socio-demographic factors associated with partial-vaccination and non-vaccination and the reasons for non-vaccination among Indian children during 1998 and 2008. Methods: Data from three consecutive, nationally-representative, District Level Household and Facility Surveys (1998–99, 2002–04 and 2007–08) were pooled. Multinomial logistic regression was used to identify individual and household level socio-demographic variables associated with the child's vaccination status. The mother's reported reasons for non-vaccination were analyzed qualitatively, adapting from a previously published framework. Results: The pooled dataset contained information on 178, 473 children 12–23 months of age; 53%, 32% and 15% were fully vaccinated, partially vaccinated and unvaccinated respectively. Compared with the 1998–1999 survey, children in the 2007–2008 survey were less likely to be unvaccinated (Adjusted Prevalence Odds Ratio (aPOR): 0.92, 95%CI = 0.86–0.98) but more likely to be partially vaccinated (aPOR: 1.58, 95%CI = 1.52–1.65). Vaccination status was inversely associated with female gender, Muslim religion, lower caste, urban residence and maternal characteristics such as lower educational attainment, non-institutional delivery, fewer antenatal care visits and non-receipt of maternal tetanus vaccination. The mother's reported reasons for non-vaccination indicated gaps in awareness, acceptance and affordability (financial and non-financial costs) related to routine vaccinations. Conclusions: Persisting socio-demographic disparities related to partial-vaccination and non-vaccination were associated with important childhood, maternal and household characteristics. Further research investigating the causal pathways through which maternal and social characteristics influence decision-making for childhood vaccinations is needed to improve uptake of routine vaccination in India. Also, efforts to increase uptake should address parental fears related to vaccination to improve trust in government health services as part of ongoing social mobilization and communication strategies.